Causes and Costs for ED Visits after Pediatric Adenotonsillectomy. (April 2015) - Curtis, Jonathan L.; Harvey, D. Brandon; Willie, Scott; Narasimhan, Evan; Andrews, Seth; Henrichsen, Jake; Van Buren, Nicholas C.; Srivastava, Rajendu; Meier, Jeremy D.
Objective: (1) Review the reasons, timing, and costs for children presenting to the emergency department (ED) after adenotonsillectomy (T&A). Study Design: Case series with chart review. Setting: Tertiary care children's hospital. Subjects and Methods: A standardized activity-based hospital accounting system was used to identify 437 children from an academic pediatric otolaryngology practice presenting to the ED after T&A from 2009 to 2012. The reason for presentation, timing after surgery, and facility costs were recorded. Results: The study cohort represented 13.3% of the 3198 patients who underwent T&A during that time period. Overall, 133 (4.2%) presented for dehydration, 106 (3.3%) presented for post-tonsillectomy hemorrhage, 65 (2.0%) for poorly controlled pain, 42 (1.3%) for fever, 29 (1.0%) for vomiting/nausea/GI discomfort, 22 (0.7%) for respiratory complications, and 12 (0.4%) for miscellaneous reasons related to the operation; 28 (0.8%) were unrelated to the T&A and excluded. Mean postoperative day at the time of ED presentation was 4.4 (95% CI, 4.1-4.7). The mean cost per patient presenting to the ED was 1420 (95% CI, 1104-1737), the most costly subgroups being those presenting with respiratory complications (2855; 95% CI, 1434-4277), hemorrhage (1502; 95% CI, 1216-1787), and dehydration (1372; 95% CI, 995-1750). The least costly subgroup was acute postoperative pain (781; 95% CI, 282-1200). Conclusion: A significant portion of children present to the ED after T&A for poorly controlled pain, dehydration, or fever. The costs from these visits are significant. Accounting for these costs in the global care for pediatric T&A could assist in calculating appropriate reimbursement for bundled payments in this climate of health care reform.